IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF UNTUK MENGEMBANGKAN NILAI KARAKTER SISWA SMP - Sarwi Sarwi; Supriyadi Supriyadi; Sudarmin Sudarmin (Universitas Negeri Semarang, 2013)
This research aims to obtain data on innovative learning models implemented in science teaching by junior high school teacher, to describe the character development of students in learning science, and to formulate recommendation for innovative learning.The research method used a survey. Area purposive random sampling technique is used to determine the 30 science teachers in the Semarang city Central Java. The subjects were learning device developed by teachers of science. Data were collected by using a list of suitable instruments, assessment formats, questionnaires, and interview guides. Data were analyzed using descriptive-qualitative techniques and evaluative analysis. Results of this research are a) applied the innovative learning of cooperative, problem based learning, problem solving, and inquiry, b) the value of the character that was developed includes honesty, cooperation, respect their opinions, critical thinking, c) the value of learning through teacher developed characters group work, laboratory work, and make a report/portfolio. Conclusion of this research that the teacher has implemented several innovative learning but has not been systematically and effectively less, and the character development of students have done. Based on the results analysis of the research recommended that school administrators need training for principals and superintendents about visionary leadership and innovative learning and training needs for teachers of educational research related to effective implementation of innovative learning and character development as well as it’s measurement.